Clinical characteristics of immunoglobulin IgG4-related sclerosing cholangitis: Comparison of cases with and without autoimmune pancreatitis in a large cohort. Issue 10 (October 2021) - Naitoh, Itaru; Kamisawa, Terumi; Tanaka, Atsushi; Nakazawa, Takahiro; Kubota, Kensuke; Takikawa, Hajime; Unno, Michiaki; Masamune, Atsushi; Kawa, Shigeyuki; Nakamura, Seiji; Okazaki, Kazuichi; et al.
Abstract: Background: The clinical characteristics of IgG4-related sclerosing cholangitis (IgG4-SC) especially without autoimmune pancreatitis (AIP) have not been investigated in a large cohort. Aims: To clarify the clinical characteristics of IgG4-SC and IgG4-SC without AIP. Methods: We retrospectively reviewed imaging, serology, other organ involvement (OOI) and histology of 872 patients with IgG4-SC who participated in a Japanese nationwide survey in 2019, and compared these items between IgG4-SC with and without AIP. Results: AIP was present in 83.7% (730/872) of IgG4-SC. In IgG4-SC, bile duct wall thickening was observed on ultrasound (528/650; 81.2%), computed tomography (375/525; 71.4%) and magnetic resonance imaging or cholangiopancreatography (290/440; 65.9%). An elevated serum IgG4 level (≥ 135 mg/dL) was found in 88.0% (322/366). IgG4-related OOI other than AIP was observed in 25.2% (211/836). The proportion of females was significantly higher in IgG4-SC without AIP (28.9% vs. 20.1%; p  = 0.025). Hilar stricture was the most common cholangiographic type in IgG4-SC without AIP (39/107; 36.4%).There were no significant differences between IgG4-SC with and without AIP in the rates of bile duct wall thickening, elevated serum IgG4 level, or IgG4-related OOI. Conclusions: The clinical characteristics of IgG4-SC was similar between IgG4-SC with and without AIP in a large cohort.